Hypocalcaemia and its contributing factors among first trimester pregnant women in an urban area in Malaysia. Issue 1 (12th February 2018) - Yeop, Noor Sharifatul Hana; Md Isa, Zaleha; Shamsuddin, Khadijah; Lin, Khor Geok; Abdullah Mahdy, Zaleha; Hassan, Haslinda; Ghazi, Hasanain
Abstract : Purpose: The aim of this study is to determine the prevalence of hypocalcaemia among first-trimester pregnant women and its contributing factors. Design/methodology/approach: A cross-sectional study was carried out among first-trimester pregnant women who were recruited during their first antenatal visit. A total of 396 respondents of age 18-40 years completed the self-administered questionnaire (socio-demographic, socio-economic, obstetric information), validated semi-quantitative food frequency questionnaire for calcium (FFQ-calcium), anthropometric measurements (weight and height) and blood test for serum calcium during their first trimester. Findings: The prevalence of hypocalcaemia based on serum calcium level of less than 2.11 mmol/L was 26.0 per cent ( n = 103). The median serum calcium level was 2.2 mmol/L (IQR, 25th and 75th percentile – 2.1 and 2.3, respectively). Milk intake of less than two glasses per day during pregnancy showed a twofold increase in developing hypocalcaemia (OR, 2.231; 95 per cent CI, 1.399, 3.588). Other than that, underweight (aOR, 2.038; 95 per cent SK, 1.088, 3.820) and obese before pregnancy (aOR, 1.954; 95 per cent SK, 1.007, 3.790) are also predictors of hypocalcaemia. Originality/value: The prevalence of hypocalcaemia among first-trimester pregnant women in this study was 26.0 per cent. Intake of two or more glasses of milk per day can help prevent hypocalcaemia at this stage of pregnancy.